Cobalt-containing hexagonal mesoporous molecular sieves (Co-HMS): Synthesis, characterization and catalytic activity in the oxidation reaction of ethylbenzene - Bhoware, Shrikant S.; Shylesh, S.; Kamble, K. R.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2006)
Cobalt-containing hexagonal mesoporous materials (Co-HMS and Co/HMS) with different cobalt content were synthesized for the first time by direct hydrothermal and post-synthesis (grafting) method. The materials were characterized in detail by X-ray diffraction, BET surface area, N-2 sorption isotherms, SEM, TEM, UV-vis and XPS techniques. Powder X-ray diffraction pattern, N2 adsorption-desorption analysis and TEM analysis show the presence of hexagonal mesoporous structure, having Type W isotherms and reveals the typical wormhole-like morphology. Spectroscopic techniques like UV-vis and XPS reveal cobalt in +2 oxidation state and tetrahedrally coordinated. Liquid phase oxidation of ethylbenzene using TBHP (70 wt%) as an oxidant shows that the catalysts are highly active, under solvent free conditions as well as under lower cobalt concentrations. Leaching studies performed by hot filtration experiments show that the cobalt catalysts prepared by hydrothermal methods are stable, while the grafted catalysts show the leaching of cobalt under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Co-HMS; ethylbenzene; HMS; hydrothermal; Oxidation

Characterization and catalytic activity of cobalt containing MCM-41 prepared by direct hydrothermal, grafting and immobilization methods - Bhoware, Shrikant S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
{Cobalt containing hexagonal mesoporous molecular sieves (MCM-41) were prepared by different methods viz., direct hydrothermal synthesis, grafting and immobilization. The calcined material was characterized by various spectroscopic tools such as powder X-ray diffraction (XRD), N-2 adsorption-desorption isotherms, Fourier transformed infra-red (Fr-IR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance UV-vis and X-ray photoelectron spectroscopy (XPS). The XRD patterns show the highly intense (100) reflection peak in the range 2-3 degrees (2 theta angle), characteristic of mesoporous material. Higher order reflection peaks suggest highly ordered mesoporous structure. N2 adsorption-desorption isotherms are of type IV according to IUPAC classification and the steep rise in the isotherms in the narrow range 3.5-4.5 of relative pressure (P/P-0) is due to the condensation of N-2 gas molecules in the pores (characteristic of mesoporous structure). In FT-IR increase in the intensity of band at 960 cm(-1) with the increase of the cobalt content in Co-MCM-41 samples indicate the incorporation of cobalt ions in the framework of MCM-41. SEM and TEM reveal spherical morphology for the cobalt substituted MCM-41. UV-vis spectra demonstrate the characteristic features of framework and extraframework cobalt in MCM-41. Cobalt is in +2 oxidation state as evidenced from UV-vis and XPS. The catalysts were tested for the side chain oxidation of ethylbenzene using 70 wt.% tert-butyl hydrogen peroxide as an oxidant with and without the use of solvent. Solvents have effect in the catalytic activity and selectivity. In the absence of solvent, substituted cobalt [
Keywords: 2-butanol; cyclohexanone; Mesoporous molecular sieves; MPV reduction

Chromium-containing small pore mesoporous silicas: synthesis, characterization and catalytic behavior in the liquid phase oxidation of cyclohexane - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Applied Catalysis A-General, 2007)
Organic-inorganic hybrid mesoporous silica materials containing chromium and various organo trialkoxysilanes (chloropropyl, vinyl, methyl) were prepared by the co-condensation method, in the presence of cetyl trimethyl ammonium surfactants. The hybrid material, containing chromium, retains one X-ray diffractogram (XRD) peak up to a molar ratio of 1: 1 between tetra ethyl orthosilicate (TEOS) and organosilane in the synthesis gel. Small pore mesoporous chromium-silica samples can be prepared from the large pore hybrid mesoporous chromium samples by calcination. By this method, the pore size of the material can be tailored into the supermicroporous region, without changing the chain length of the surfactant used in the assembly process, as judged from the XRD and N-2 sorption isotherms. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups, such that the chloro propyl and vinyl pendant mesoporous material show more pore size shrinkage than the smaller methyl pendant units. Because of the tailorable pore size and with better textural characteristics, the chromium samples show better catalytic activity in the aerial oxidation reaction of cyclohexane than the conventional chromium-containing mesoporous material, like Cr-MCM-41, under a solvent free system. Among the porous chromium catalysts, the samples prepared using chloro propyl silane show higher cyclohexane conversion and cyclohexanone selectivity and behave as a true heterogeneous catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chromium; Cyclohexane; Oxidation; small pore silicas

Catalytic activity of cobalt containing MCM-41 and HMS in liquid phase oxidation of diphenylmethane - Bhoware, Shrikant S.; Kamble, K. R.; Singh, A. P. (Catalysis Letters, 2009)
Cobalt containing MCM-41 and HMS were synthesized by direct hydrothermal (DHT) and post synthesis methods (grafting and immobilization). The catalytic activity of these materials was investigated in the liquid phase oxidation of diphenylmethane at 80 A degrees C with TBHP (70 wt%) as oxidant. Comparative study of cobalt containing MCM-41 and HMS was carried out to reveal the catalytic performance of framework, extraframework and immobilized cobalt species. The role of the solvent in the performance of catalyst was examined with different polar and non polar solvents. Oxidation of diphenylmethane in solvent free media (under similar reaction conditions) shows formation of hydroxy derivatives of benzophenone in addition to main product (benzophenone). Hundred percent selectivity to benzophenone was obtained when the reaction was carried out in solvent.
Keywords: diphenylmethane; HMS; Immobilization; MCM-41; XRD

Catalytic aerobic oxidation of cyclohexane and ethyl benzene over chromium-containing mesoporous organosilicas - Singh, A. P.; Torita, N.; Shylesh, S.; Iwasa, N.; Arai, M. (Catalysis Letters, 2009)
Chromium-containing ethane-bridged hybrid periodic mesoporous organosilicas (Cr-PMO) were synthesized using 1,2-bis(triethoxysilyl) ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts as surfactants by two different synthesis routes. PXRD and N(2) adsorption-desorption analysis shows that the original structure of the materials is maintained after chromium substitution while spectroscopic study proves the incorporation of chromium in the frame wall positions and show the existence of Cr(2)O(3) species in the mixed silica source (BTEE-TEOS) synthesized chromium samples. The catalytic activity of the newly developed chromium samples was evaluated in the liquid phase oxidation of cyclohexane and ethylbenzene using air as an oxidant. Further, the Cr-PMO samples exhibited better cyclohexane conversion and cyclohexanone selectivity than the conventional Cr-MCM-41 and other metal-containing MCM-41 samples. The exceptional activity of the new chromium-containing molecular sieves is attributed to the hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of substrate to the active framework chromium sites.
Keywords: Cr-MCM-41; Cyclohexane; Ethyl benzene; Organosilicas; Oxidation

Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole

Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Covalently anchored 2,4,6-triallyloxy-1,3,5-triazine Pd(II) complex over a modified surface of SBA-15: catalytic application in hydrogenation reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
Highly efficient and reusable SBA-15-TAT-Pd(II) has been synthesized by anchoring a 2,4,6-triallyloxy-1,3,5-triazine (TAT) complex over the organo-functionalized surface of SBA-15. The physiochemical properties of the organo-functionalized catalyst were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption measurement isotherm, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, DRS UV-visible, SEM and TEM. XRD & N-2 sorption were analyzed to find out the textural properties of the synthesized catalyst and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The electronic environment and oxidation state of Pd in SBA-15-TAT-Pd(II) were monitored by XPS and DRS UV-visible techniques. The catalytic activity of the synthesized catalyst SBA-15-TAT-Pd(II) was screened for hydrogenation reactions and shows higher catalytic activity with good turnover numbers (TON) under optimized experimental conditions with maximum conversion (> 99%) and selectivity (100%). The anchored solid catalyst can be recycled efficiently and reused upto five times without major loss in reactivity.

Correlating the role of hydrophilic/hydrophobic nature of Rh(I) and Ru(II) supported organosilica/silica catalysts in organotransformation reactions - Lazar, Anish; George, Shoy C.; Jithesh, P. R.; Vinod, C. P.; Singh, A. P. (Applied Catalysis A-General, 2016)
Highly reactive and hydrophobic triphenyl phosphine based rhodium(I) and ruthenium(II) organometallic complexes over benzene containing periodic mesoporous organosilica (PMOB) have been synthesized. This has been achieved by the immobilization of neat metal complexes like RhCl(PPh3)(3) [Wilkinson catalyst], RuHCl(CO)(PPh3)(3) and RuCl2(PPh3)(3) over aminofunctionalized PMOB to get RhCl(PPh3)(2)-PrNH2PMOB, RuHCl(CO)(PPh3)(2)-PrNH2PMOB and RuCl2(PPh3)(3)-PrNH2PMOB, respectively. The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption analyses, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, SEM, TEM and contact angle measurements. The XRD and N-2 sorption analyses showed excellent textural properties with ordered mesoporous channel structure of all synthesized catalysts. The organic moieties anchored in PMOB were confirmed by C-13 CPMAS NMR and Fr-IR spectroscopy with Si-29 CPMAS NMR spectroscopy providing the information about the degree of functionalization of surface silanol groups with organic moiety. The Rh(I) and Ru(II) complexes supported on MCM-41/SBA-15/PMOE (ethane-PMO) were synthesized, and their catalytic activities in hydrogenation and sulfoxidation reactions were compared with Rh(I) and Ru(II) complexes supported on PMOB. The results show that PMOB based catalysts exhibit higher activities and selectivities than MCM-41/SBA-15/PMOB supported catalysts, neat homogeneous complexes and without catalyst. The better catalytic performance of PMOB based catalyst is attributed to the hydrophobic nature and high surface area of the PMOB support. The recycling studies of anchored catalysts show no major deactivation of the catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Hydrogenation and sulfoxidation; Hydrophobic; Periodic mesoporous organosilica